Connective tissue cells of the skin: heterogeneity of fibroblasts and general properties of their subpopulations - Maievskyi, O.Ye.; Tverdokhlib, I.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Directing of experimental and clinical research requires integration of information on morphological and functional features of organs and tissue structures. One of the examples of such integration is the analysis of the histophysiology of the skin, in particular dermal fibroblasts – a mandatory cellular component of the dermis. They not only synthesize and organize the components of the extracellular matrix of the dermis, but also interact with each other and with other types of cells, playing a decisive role in the regulation of skin histophysiology. Other resident cells include epidermal, vascular, and nerve cells. In addition, the skin contains various cells of hematogenous origin. They contain a constitutive population of dendritic cells and a more dynamic population of leukocytes, which includes monocytes (macrophages), neutrophils, and lymphocytes. Dermal fibroblasts are a dynamic and diverse population of cells whose functions in skin in many respects remain unknown. Normal adult human skin contains at least three distinct subpopulations of fibroblasts, which occupy unique niches in the dermis. Fibroblasts from each of these niches exhibit distinctive differences when cultured separately. Specific differences in fibroblast histophysiology are evident in papillary dermal fibroblasts, which reside in the superficial dermis, and reticular fibroblasts, which reside in the deep dermis. Both of these subpopulations of fibroblasts differ from the fibroblasts that are associated with hair follicles. Fibroblasts engage in fibroblast-epidermal interactions during hair development and in interfollicular regions of skin. They also play an important role in cutaneous structural transformations.